UTILITY OF NEUROSTEROIDS IN RESTORATION OF EFFECTS OF ETHANOL: A CRITICAL EVALUATION (International Journal of Food and Nutritional Sciences, 2022)
The article will focus on various physiological conditions linked to the activity of the hypothalamic-pituitary-adrenal (HPA) and hypothalamic-pituitary-gonadal (HPG) axes, the consequences of chronic ethanol contact, as well as behavioural consequences for how neurosteroids affect sensitivity to ethanol. The alteration of ethanol impacts by neuroactive steroids has so far been mostly focused on pathways involving -aminobutyric acid receptors. Although NMDA receptor pathways are becoming more prominent in the literature, it would be appropriate to discuss this complicated data individually. In order to highlight the divergent neuroactive steroid pharmacology, receptor mechanisms are highlighted in this review along with a quick discussion of some NMDA receptor processes. Overall, the data imply that neurosteroids are essentially universal inhibitory neurotransmission modulators. According to certain behavioural studies, neurosteroids appear to impact sensitivity to ethanol in particular brain regions. This effect may be connected to how well and effectively ethanol can stimulate the release of receptors and raise neurosteroid concentrations. Although some investigations have revealed a direct interaction between ethanol and neuroactive steroids at similar receptor binding sites, this idea is still debatable. The precise method through which neuroactive steroids could modify the effects of ethanol in particular behavioural tasks is still impossible to pinpoint.